In-vitro Evaluation of Chitosan - Hydroxyapatite Nanocomposite Scaffolds as Bone Substitutes with Antibiofilm Properties - Lipton, Anuj Nishanth; Fathima, A.; Vincent, S. (2021)
An opaque, white chitosan/ Hydroxyapatite nanocomposite was prepared by a simple blend method. Morphology, pore size and dispersion of nano-hydroxyapatite in chitosan matrix were visualized using SEM images. The FTIR and SEM with EDX analysis confirmed the bony apatite layer was formed on the outside of the composite. Porosity measurements and water uptake studies of the nanocomposite were evaluated which revealed the maximum porosity of 80% to 92% in the chitosan: hydroxyapatite nanocomposite at the ratio of 20:80. The results also showed that water absorption ability was inversely proportional to the hydroxyapatite present in the nanocomposite. The porosity of prepared nanocomposite was corresponding to the cancellous bone porosity of 50% to 90% suggesting possible applications in bone transplantation. The nanocomposite exhibited antibacterial activity towards the tested Gram-negative and Gram-positive species of bacteria and reduced the bacterial adhesion in biofilm formation.